Increased Numb protein expression predicts poor clinical outcomes in esophageal squamous cell carcinoma patients. Issue 1 (2nd January 2018) - Liu, Zhenguo; Luo, Canqiao; Yang, Weixiong; Wang, Kefeng; Hu, Chuang; Zou, Jianyong; Zhu, Hua; Fu, Liwu; Nie, Jing; Cheng, Chao
ABSTRACT: Numb is a protein whose asymmetric segregation during cell division determines cell fate and has numerous functions relevant to multiple fields of study, including developmental neurobiology and cancer biology. Little is known about the role of Numb in esophageal squamous cell carcinoma (ESCC), the predominant histological esophageal carcinoma in Asian populations. In this study, we focused on the expression and biologic functions of Numb in the context of ESCC. From analysis of tissue microarrays with 212 patients, it was found that Numb was significantly upregulated in ESCC tissues compared with corresponding non-cancerous tissues. Kaplan-Meier survival analysis suggests that higher expression of Numb was significantly associated with a high tumor recurrence (p = 0.015) and poor overall post-surgical survival (p = 0.016). Using multiple Cox regression, the expression of Numb was determined to be an independent predictor of poor prognosis. When siRNA was used to knockdown Numb in ESCC cell lines, there was a consistent increase in caspase-3 dependent apoptosis and inhibition of cellular proliferation, as well as downregulation of expression of the cancer stem cell markers Oct-4, SOX-2 and Nanog. In addition, downregulated Numb expression was not significantly associated with the migration of ESCC cells. These results indicate that Numb acts as an oncoprotein and has potential as a novel prognostic biomarker and therapeutic target in ESCC patients.